(untitled) (Marketing Journal, 2026)
Abstract This article examines the institutional foundations for the formation of regional investment potential. Particular attention is given to key institutional factors, including regulatory environment, governance systems, investment infrastructure, and investment support mechanisms. The study identifies priority directions for improving institutional conditions to enhance regional investment attractiveness and proposes scientifically grounded recommendations. The findings contribute to strengthening institutional capacity and improving regional investment development. Keywords: investment potential, institutional environment, regional development, investment attractiveness, institutional mechanisms, investment infrastructure.